2020
DOI: 10.1200/jco.2020.38.15_suppl.6002
|View full text |Cite
|
Sign up to set email alerts
|

Final overall survival (OS) results from SOLO2/ENGOT-ov21: A phase III trial assessing maintenance olaparib in patients (pts) with platinum-sensitive, relapsed ovarian cancer and a BRCA mutation.

Abstract: 6002 Background: SOLO2 (ENGOT ov-21; NCT01874353) showed that maintenance therapy with the PARP inhibitor olaparib in pts with platinum-sensitive relapsed ovarian cancer (PSROC) and a BRCA mutation (BRCAm) led to a statistically significant improvement in median progression-free survival (PFS) of 13.6 months vs placebo (hazard ratio [HR] 0.30). Time to second progression or death significantly improved (Pujade-Lauraine et al Lancet Oncol 2017) and a quality-adjusted PFS benefit was seen (Friedlander et al Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 0 publications
4
76
0
3
Order By: Relevance
“…Hematologic AEs may be considered a class effect of PARP inhibitors, with anemia being the most common (any grade: 21-50%; grade ≥3: 5-25%), followed by thrombocytopenia (any grade: < 10-61%; grade ≥3: < 3-34%), and neutropenia (any grade: 5-30%; grade ≥3: 4-20%). The incidence of myelodysplastic syndrome or acute myeloid leukemia observed with all three PARP inhibitors is low (1-2%) [20,21,38]; however, in the final OS analysis of SOLO2, the incidence was 8% with olaparib (mean treatment duration: 29.1 months) versus 4% with placebo (mean treatment duration: 18.6 months) [43].…”
Section: Safety Of Maintenance Therapy For Recurrent Ovarian Cancermentioning
confidence: 92%
See 2 more Smart Citations
“…Hematologic AEs may be considered a class effect of PARP inhibitors, with anemia being the most common (any grade: 21-50%; grade ≥3: 5-25%), followed by thrombocytopenia (any grade: < 10-61%; grade ≥3: < 3-34%), and neutropenia (any grade: 5-30%; grade ≥3: 4-20%). The incidence of myelodysplastic syndrome or acute myeloid leukemia observed with all three PARP inhibitors is low (1-2%) [20,21,38]; however, in the final OS analysis of SOLO2, the incidence was 8% with olaparib (mean treatment duration: 29.1 months) versus 4% with placebo (mean treatment duration: 18.6 months) [43].…”
Section: Safety Of Maintenance Therapy For Recurrent Ovarian Cancermentioning
confidence: 92%
“…Although OS was numerically longer with the addition of bevacizumab maintenance to chemotherapy versus chemotherapy alone, no statistically significant survival benefit was observed in OCEANS ( [42]. Median OS in SOLO2 was also longer with olaparib than placebo (51.7 vs 38.8 months; HR 0.74 [95% CI 0.54-1.00]; P = 0.0537) [43]. OS data for NOVA and ARIEL3 are not yet mature.…”
Section: Overall Survivalmentioning
confidence: 98%
See 1 more Smart Citation
“…The median prior line was 5 (3)(4)(5)(6)(7)(8) in the exploratory multi-line therapy group. Ultimately therapeutic evaluation showed that two patients achieved partial response (PR), one patient achieved stable disease (SD) and three patients had progressive disease (PD), yielding the objective response rate (ORR) of 33.3%…”
Section: E Cacy and Hrd Statusmentioning
confidence: 99%
“…How to prolong the platinum free interval (PFI) becomes one of the breakthrough points in ovarian cancer treatment. Recently, poly ADP-ribose Polymerase (PARP) inhibitors have changed the treatment paradigm for ovarian cancer that can signi cantly improve the platinum free interval, and nally prolong the overall survival of patients with BRCA mutation [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%